Fathers and Sons in the Arab Middle East - Cohen-Mor, D. author. aut Link
X, 234 p.
Keywords: Drawing on insights from psychology, sociology, anthropology, religion, history, and literature, this book examines early and contemporary writings of male authors from across the Arab world to explore the traditional and evolving nature of father-son relationships in Arab families.